Replacing Sugar by Date Syrup in Gaz and Investigation of Texture Properties - Fateme Raiesi Ardali; Zahra Nilchian; Saeid Ahmadi; Mohammad Ali Shariati; Mina Akbarian (Chemical Engineering Diponegoro University, 2014)
Date Syrup is a natural sweetener that is suitable replacement for sugar in food stuffs formulation. In this Research Amounts of 25-100 percent of sugar in Gaz formulation were replaced with date syrup and to study effect of its use in product formulation, characteristics of texture, color and sensory analyse of treatments were investigated. Statistical analyse of data was also done by SPSS software and Dankan test. The results of this research showed that amount of used date syrup in formulation had a significant effect on color parameters (L*,a*,b*), texture characteristics and sensory analyse of samples. By increase of date syrup in Gaz formulation, samples texture became softer than control sample and yellowness and redness index of samples were increasedDoi: DOI: 10.12777/ijse.6.1.11-15 [How to cite this article: Shafiei, Z., Hojjatoleslami, M., Soha, S., and Shariati, M.A. 2014. The Influence of Malt Extraction Adding to UF Fresh Low Fat Cheese on Its Textural Properties. International Journal of Science and Engineering, 6(1):57-60. Doi: 10.12777/ijse.6.1.11-15